Reliability and Validity of the Persian version of the Clock Drawing Test in Iranian Patients with Idiopathic Parkinson's Disease - Mahmoudi Asl, Aysan; Mehdizadeh, Maryam; Raeesi Roudbari, Parvin; Habibi, Seyed-Amirhasan; Niazi Khatoon, Javad; Taghizadeh, Ghorban (Journal of Clinical Physiotherapy Research, 2018)
Introduction: The evaluation of cognitive impairment in people with Parkinson’s disease is important for timely use of medical and rehabilitation services. To achieve this goal, this study was conducted to verify the reliability and validity of the Persian Version of the clock drawing test (CDT). Materials and Methods: In the first session, the cognitive function of 180 subjects with Parkinson's disease and mean age (±SD) of 57.6 (±7.8) were evaluated using the CDT. The test was redone within 7 to 10 days. The test-retest and inter-tester reliability were evaluated by the IntraClass Correlation Coefficient (ICC). The concurrent validity was also measured through the relationship between the CDT and the Clinical Dementia Rating scale (CDR), the Parkinson Disease Questionnaire-8 (PDQ-8) and the Mini-Mental Status Examination (MMSE). Results: An acceptable level of reliability between the raters (ICC=0.94 (95% CI, 0.92–0.97)) and test-retest (ICC=0.92 (95% CI, 0.90–0.95)) was obtained among these patients. There was also a moderate to high correlation between the CDT with CDR, and the PDQ and MMSE. Conclusion: The results of this study showed that the clock drawing test has a high reliability and an acceptable validity for measuring cognitive function in Iranians with idiopathic Parkinson's disease. Keywords: Clock Drawing Test, Cognitive Function, Parkinson's disease, Validity and Reliability